2012
DOI: 10.1111/j.1460-9568.2012.08143.x
|View full text |Cite
|
Sign up to set email alerts
|

Do proconvulsants modify or halt epileptogenesis? Pentylenetetrazole is ineffective in two rat models of temporal lobe epilepsy

Abstract: In patients at risk of developing epilepsy after an initial precipitating injury to the brain, the epileptogenic latent period may offer a window of opportunity for initiating potential antiepileptogenic therapy in an attempt to prevent epilepsy from developing. One potential target for antiepileptogenesis is the development of neuronal hyperexcitability during the latent period. Surprisingly, some recent studies in models of temporal lobe epilepsy (TLE) have suggested that proconvulsant drugs could have favou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…We have recently shown in rats that the threshold to seizures induced by the GABA A receptor antagonist pentylenetetrazol (PTZ) decreases during the latent period following status epilepticus (SE) induced by either pilocarpine or kainate, indicating that the PTZ seizure threshold may be used as a biomarker of changes in GABAergic transmission during epileptogenesis . In the present experiments in mice, before administration of pilocarpine, average PTZ seizure thresholds in controls ranged from 55mg/kg PTZ for the first myoclonic twitch to 112mg/kg for tonic hindlimb extension (Fig ), which was often followed by death of the animals.…”
Section: Resultsmentioning
confidence: 67%
“…We have recently shown in rats that the threshold to seizures induced by the GABA A receptor antagonist pentylenetetrazol (PTZ) decreases during the latent period following status epilepticus (SE) induced by either pilocarpine or kainate, indicating that the PTZ seizure threshold may be used as a biomarker of changes in GABAergic transmission during epileptogenesis . In the present experiments in mice, before administration of pilocarpine, average PTZ seizure thresholds in controls ranged from 55mg/kg PTZ for the first myoclonic twitch to 112mg/kg for tonic hindlimb extension (Fig ), which was often followed by death of the animals.…”
Section: Resultsmentioning
confidence: 67%
“…Furthermore, we have previously shown that the sensitivity of the BLA to electrical stimulation is not affected by the estrous cycle in rats [15] so that the stage of the estrous cycle was not determined in the present experiments. Similarly, the PTZ seizure threshold is not affected by the estrous cycle in rats [16,17].…”
Section: Animalsmentioning
confidence: 99%
“…Furthermore, although the estrous cycle is thought to affect seizure threshold [198,199], thus causing variability when using females, this is not true for all types of seizure threshold in rodents. For instance, PTZ seizure thresholds determined by timed intravenous infusion of this convulsant is not affected by the estrous cycle in rodents, while estrous cycle-dependent changes (and significant differences between females and males) were found for bicuculline seizure thresholds [200,201]. Similarly, the ADT in amygdala kindled female rats did not change significantly during the estrous cycle [202], while small but statistically significant changes were reported for electroshock seizure thresholds (EST) in rats [203].…”
Section: Role Of Sex For Inter- and Intrastrain Differencesmentioning
confidence: 99%